Violence, Politics, and Gender in Early Modern England
XII, 264 p.
Keywords: This book engages in an interdisciplinary study of the establishment and entrenchment of gender roles in early modern England. Drawing upon the methods and sources of literary criticism and social history, this edited volume shows how politics at both the elite and plebeian levels of society involved violence that either resulted from or expressed hostility toward the early modern gender system. Contributors take fresh approaches to prominent works by Shakespeare, Middleton, and Behn as well as discuss lesser known texts and events such as the execution of female heretics in Reformation Norwich and the punishment of prostitutes in seventeenth-century London to draw new conclusions about gender in early modern England.